ROS accumulation by PEITC selectively kills ovarian cancer cells via UPR-mediated apoptosis - Hong, Yoon-hee; Uddin, Md. Hafiz; Jo, Untek; Kim, Boyun; Suh, Dong Hoon; Kim, Hee Seung; Song, Jiyoung; Song, Yong Sang (Frontiers in Oncology, 2015)
Unfolded protein response (UPR) is crucial for both survival and death of mammalian cells, which is regulated by reactive oxygen species (ROS) and nutrient depletion. In this study, we demonstrated the effect of ROS-accumulation, induced by β-phenethyl isothiocyanate (PEITC), on UPR-mediated apoptosis in ovarian cancer cells. We used ovarian cancer cell lines, PA-1 and SKOV-3, with different p53 status (wild- and null-type, respectively). PEITC caused increased ROS-accumulation and inhibited proliferation selectively in ovarian cancer cells, and glutathione (GSH) depletion in SKOV-3. However, PEITC did not cause any effect in normal ovarian epithelial cells and peripheral blood mononuclear cells. After 48 h of PEITC treatment (5 μM), apoptotic cell death was shown to increase significantly in the ovarian cancer cells and not in the normal cells. The key regulator of UPR-mediated apoptosis, CHOP/GADD153 and endoplasmic reticulum resident chaperone BiP/GRP78 were parallely up-regulated with activation of two major sensors of the UPR [PERK and ATF-6 in PA-1; PERK, and IRE1α in SKOV-3) in response to ROS accumulation induced by PEITC (5 μM). ROS scavenger, N-acetyl-L-cysteine (NAC), attenuated the effect of PEITC on UPR signatures (P-PERK, IRE1α, CHOP/GADD153, and BiP/GRP78), suggesting the involvement of ROS in UPR-mediated apoptosis. Altogether, PEITC induces UPR-mediated apoptosis in ovarian cancer cells via accumulation of ROS in a cancer-specific manner.